PENGEMBANGAN MICROCONTENT DI BIDANG FOOD & BEVERAGE PRODUCT UNTUK MAHASISWA D4 PENGELOLAAN PERHOTELAN - Gede Esa Putra Putra; A A Ngurah Yudha Martin Mahardika; Trianasari (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
This study aimed to develop a Microcontent-based learning media integrated with English for Food and Beverage in the Food and Beverage Product course for students of the Applied Bachelor of Hotel Management program. The study employed a development research method with a descriptive qualitative approach, consisting of four stages: needs analysis, Microcontent video prototype development, classroom trial, and evaluation. The participants were 19 seventh-semester students of the Applied Bachelor of Hotel Management program. Data were collected through open-ended questionnaires, observations, and documentation. The results showed that the Microcontent was perceived as clear, engaging, and easy to understand. It helped students improve their understanding of practical procedures and English vocabulary related to Food and Beverage operations. Students identified the main strengths of the media as its concise presentation, flexibility, and accessibility for repeated learning. However, some students noted that the short video duration limited the depth of explanation for certain topics. These findings suggest that Microcontent has the potential to enhance the effectiveness of practical learning and support independent learning in hospitality vocational education.